2013
DOI: 10.4103/2230-8229.122009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and the relationship of oral mucosal lesions in tobacco users and denture wearers in the North Indian population

Abstract: Aim:The aim of the present study was to determine the prevalence and the relationship of oral mucosal lesions in tobacco users and denture wearers in a North Indian population.Materials and Methods:The study comprised 3,749 patients attending the Department of Oral Medicine and Radiology, Jodhpur Dental College General Hospital between September 2008 and December 2012, for the treatment of dental problems other than oral mucosal lesions. The ages ranged from 28 years to 83 years, with a mean age of 49.7 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
10
3
1
Order By: Relevance
“…The prevalence of Angular cheilitis in this study was about 17%, which was higher than that of the study of Patil et al (2013), 1.9% and higher than the prevalence reported by Pegah et al (2012) who reported 2.5% prevalence of angular cheilitis. The study of Mujica et al (2008) reported the prevalence of angular cheilitis to be 5%.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The prevalence of Angular cheilitis in this study was about 17%, which was higher than that of the study of Patil et al (2013), 1.9% and higher than the prevalence reported by Pegah et al (2012) who reported 2.5% prevalence of angular cheilitis. The study of Mujica et al (2008) reported the prevalence of angular cheilitis to be 5%.…”
Section: Discussioncontrasting
confidence: 80%
“…The prevalence of traumatic keratosis was about 22% in this study, and this result is slightly higher than that reported by Patil et al (2013) who reported keratosis as 19.2%.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Nenhuma associação significativa foi encontrada entre estomatite protética e achados microbiológicos, idade ou tipo das próteses, presença de prótese anterior e hábito de fumar. Patil et al 10 encontraram relação estatisticamente significante entre uso de prótese e candidíase.…”
Section: Resultsunclassified
“…The extensive use of tobacco products will multiply the incidence of tobacco-related cancer in the state and can encumber the state's health system. 15 The sale of smokeless tobacco has been prohibited in the state. The present study showed that in spite of the ban, the use of smokeless tobacco products was high among male migrants.…”
Section: Discussionmentioning
confidence: 99%